PELATIHAN PEMBUATAN MINUMAN BERBAHAN DASAR RUMPUT LAUT - Mutia Kartika; Prita Laura; Rosianna Sianipar; Yustisia Kristiana (LPSDI Bina Patria, 2025)
The utilization of seaweed in the food and beverage industry is increasing due to its rich nutritional content and various health benefits. This study examines the potential use of Undaria pinnatifida (Wakame) as a base ingredient in innovative healthy beverage products. Wakame, which is known to be rich in nutrients such as fiber, vitamins and minerals, is used together with other natural ingredients, such as honey and lemon, to create a refreshing drink with high health value. The implementation method used is training and mentoring that facilitates the discussion of knowledge and knowledge to students of SMK IPTEK South Tangerang with the aim of improving their skills in processing seaweed as a product innovation. The results of the training showed an increase in participants' understanding and skills, as reflected in the pre-test and post-test data. This training can be a promising first step for local-based business development with broad market potential. The next step is to develop further training that covers marketing aspects, packaging techniques, and collaboration with industry players to increase product competitiveness in domestic and international markets